The Application of Islamic Business Ethics and The Creativity of Waroeng Special Sambal on Sales Profit - Hana Rafita Sari; Irmala Yulia Widyatantri (FEBI UIN Sunan Kalijaga, 2022)
This study aims to describe research respondents' data, to determine the effect of Islamic business ethics and creativity on sales profits at Waroeng Special Sambal. The number of samples in this study were 15 respondents. The statistical method uses multiple linear regression analysis. Based on the results of the study, it can be concluded that the variables of Islamic business ethics and creativity simultaneously affect sales profits, hypothesis testing is obtained F count = 9.642 > F table = 3.68 with a significance of 0.003 <0.05. And partially the Islamic business ethics variable has no significant effect on sales profits, while the creativity variable has a significant effect on sales profits. Islamic business ethics and creativity affect sales profits by 61.6%.